POLICING THE DIGITAL REALMS: REFLECTION ON COMMUNITY POLICING DISCOURSES IN THE DIGITAL REALMS - Kurniawan, Kukuh S. (International Review of Humanities Studies, 2021)
This paper tends to reconceptualize community policing as the embodiment of community oriented policing related to the shifting definition of community. In response to these dynamics, the issue of the relationship between the digital realm and community policing that has been implemented is important to study. The study is expected to reflect thoughts on the issue of crime in the digital realm, concepts and models of community policing, as well as ways to increase the potential of contextual Community Policing. How to increase the potential for community policing so that it can be used in dealing with problems in the digital realm according to the development of the digital realms, especially the rhetoric of Revolution 4.0 in contemporary Indonesia.